2018
DOI: 10.1016/j.landusepol.2018.08.043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transport cost on housing affordability: Experiences from the Bandung Metropolitan Area, Indonesia

Abstract: Transport and housing costs are interrelated due to their substantial share of household budgets. In many cases, households are making trade-offs by either spending more on housing in the inner city with lower transport costs or choosing more affordable housing in suburban areas, with higher commuting cost. This paper aims to examine housing and transport affordability by exploring middle to low-income household's transport and housing expenses in the Bandung Metropolitan Area (BMA), Indonesia. Households in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 52 publications
2
14
1
Order By: Relevance
“…The results of [Survey A -2] show that the travel distance to public facilities has actually shortened and the travel costs have reduced after moving. These reductions in travel distance and costs due to moving to a downtown area are consistent with a previous study [50] that confirmed that there is high accessibility in the downtown area and a resulting low cost of movement. These survey results suggest that the downtown area is more convenient than suburban high-rises that offer a high level of safety against tsunamis, making the residents satisfied with the surrounding environment.…”
Section: Discussionsupporting
confidence: 92%
“…The results of [Survey A -2] show that the travel distance to public facilities has actually shortened and the travel costs have reduced after moving. These reductions in travel distance and costs due to moving to a downtown area are consistent with a previous study [50] that confirmed that there is high accessibility in the downtown area and a resulting low cost of movement. These survey results suggest that the downtown area is more convenient than suburban high-rises that offer a high level of safety against tsunamis, making the residents satisfied with the surrounding environment.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, this may also lead to long distance commuting and traffic congestion (Zhao and Hu, 2019), and cause air pollution, particularly for people who travel by private vehicles (Cao et al, 2017). To some extent, these results also reflect the combined issue of car dependence and housing affordability (Cao and Hickman, 2018;Dewita et al, 2018Dewita et al, , 2020, as well as inferring potential issues associated with transport-related social inequity (Cao, 2019;Cao andHickman, 2019, 2020;Zhao and Cao, 2020;Zhang et al, 2018). On the other hand, the expansion of jobs from the typical employment area to the surrounding area has relieved traffic congestion in the city.…”
Section: Spatial Distributionmentioning
confidence: 99%
“…Finding a strategic land located at a decent rate is the most critical step in the development of affordable housing schemes (Mulliner and Algrnas, 2018). Land cost is the single biggest factor that majorly affects the costing of a housing project (Dewita et al , 2018). Commonly, low-price lands are located far from the infrastructural facilities such as transportation, hospitals, schools, shopping centres and employment (Opoku and Abdul-Muhmin, 2010).…”
Section: Model For Framework Of Factual Situation In Housing Supply and Demandmentioning
confidence: 99%